TEMPO AND MODE OF MATING SYSTEM EVOLUTION BETWEEN INCIPIENT CLARKIA SPECIES - Pettengill, James B.; Moeller, David A. (Evolution, 2012)
Mating systems are among the most labile characteristics of flowering plants, with transitions frequently occurring among populations or in association with speciation. The frequency of mating system shifts has made it difficult to reconstruct historical evolutionary dynamics unless transitions have been very recent. Here, we examine molecular and phenotypic variation to determine the polarity, timescale, and causes of a transition between outcrossing and self-fertilization in sister subspecies of Clarkia xantiana. Phylogenetic analyses and coalescent-based estimates of the time to most recent common ancestor indicated that outcrossing is ancestral to self ing and that there has been a single origin of self ing. Estimates of divergence time between outcrossing and selfing subspecies were 10,000 (95% CI [credible interval]: 3169–66,889) and 65,000 years ago (95% CI: 33,035–151,448) based on two different methods, suggesting a recent and rapid evolutionary transition. Population genetic data indicated that the transition to selfing was associated with a 80% reduction in molecular diversity, which is much greater than the 50% reduction expected under a shift from obligate outcrossing to obligate self-fertilization alone. Our data also suggest that this severe loss of diversity was caused by colonization bottlenecks. Together with previous studies, evidence for reproductive assurance in xantiana now connects variation in plant-pollinator interactions in the field to phenotypic and molecular evolution.